Reconstruction Of The Authority To Seize Evidence By Military Police Investigators In Corruption Crimes To Realize Legal Certainty - Tambunan, Anton Maruli; Latif, Abdul; Kristiawanto , Kristiawanto (Advances In Social Humanities Research, 2025)
Seizure of evidence is one of the key instruments in the law enforcement process, including in corruption crimes involving members of the military. However, the authority of Military Police (PM) investigators in conducting seizures still faces various normative and procedural obstacles. This research aims to analyze the legal construction governing this authority and offer an ideal reconstruction model to ensure legal certainty. By using normative juridical methods and a multidimensional approach - namely legislative, historical, comparative, and conceptual approaches - this research reveals the existence of inconsistencies between the Military Justice Law, the KPK Law, and the Corruption Crime Law, which have implications for the uncertainty of the authority of PM investigators in corruption cases, especially in the context of military-civilian connectivity. This research offers a legal reconstruction that includes regulatory harmonization, the formation of a cross-agency connectivity team, standardized confiscation SOPs, and strengthening the supervision of the military court. The novelty of this research lies in the focus of specific studies on confiscation by PM investigators in corruption crimes and the development of applicable operational legal models. The contribution is significant for the development of military criminal law and law enforcement system reform within the TNI.